Experience of frontline nurses who managed the COVID-19 crisis: A qualitative study - Moradian, Seyed Tayeb; Mahmoudi, Hosein (Frontiers in Public Health, 2023)
Background The health system was challenged during the COVID-19 pandemic. Nurses, as part of the health system, were expected to manage themselves in a situation where everyone was in crisis and to be able to do their work quietly and calmly. This study was conducted to show how Iranian nurses faced the COVID-19 crisis. Methods In a qualitative content analysis study, 16 participants, including eight nurses, five supervisors, and three head nurses of a university hospital in Tehran, Iran, were interviewed between February and December 2020. Using purposive sampling, nurses who were working with patients with COVID-19 were selected to be involved. Data were analyzed using MAXQDA 10 software, and codes were categorized based on similarities and differences. Finding Data analysis revealed 212 codes. These codes were classified based on similarities and differences in 16 categories, and four main themes emerged: unpreparedness, positive adaptation, negative coping, and reorganization. Conclusion Since nurses are on the frontline in times of biological disaster, the COVID-19 pandemic provided an opportunity to demonstrate the role of nurses in reducing the burden of disease, identifying problems and opportunities, and planning appropriate interventions.